The mechanism of digital feedback on health information anxiety among older adults: information processing self-efficacy as a mediating variable - Zhu, Yang; Wang, Xin; Zhang, Xiao; Li, Yan; Chen, Yepeng (Frontiers in Public Health, 2025)
BackgroundDigital feedback emerges as a significant variable influencing health information anxiety among older adults, and information processing self-efficacy also plays a crucial role in this process. This study aims to clarify the logical relationships among digital feedback, health information anxiety, and information processing self-efficacy.MethodsGuided by the “hypothesis testing” paradigm, this empirical study was based on the construction of a mediation model to examine how digital feedback influences health information anxiety among older adults. Stratified random sampling in conjunction with probability proportional to size (PPS) sampling was used to survey a sample of 1,713 older adults from 30 Chinese cities. Exploratory factor analysis (EFA), correlation analysis, causal steps approach, and the Bootstrap method were employed to test the mediating model. Mediation analysis was conducted using the PROCESS macro, and in-depth interviews were carried out to explore the underlying mechanisms of this process.ResultsThe study found that digital feedback had a negative effect on health information anxiety among older adults (β = −0.396, p < 0.001), while it had a positive impact on their information processing self-efficacy (β = 0.700, p < 0.001). Additionally, information processing self-efficacy had a negative effect on health information anxiety among older adults (β = −0.401, p < 0.001). The analysis further revealed that the relationship between digital feedback and health information anxiety was partially mediated by information processing self-efficacy (β = −0.2806, SE = 0.0157, 95% CI = −0.3115, −0.2503).ConclusionsDigital feedback not only directly mitigates HIA among older adults but can also indirectly reduce health information anxiety by enhancing their information processing self-efficacy. It should be emphasized that inappropriate digital feedback from children, such as insufficiently thorough instruction or lack of patience, may exacerbate health information anxiety among older adults. Therefore, children should actively participate in the digital feedback process, demonstrate patience during feedback, and provide targeted assistance based on the actual needs of older adults. This approach can help older adults maintain their physical and mental wellbeing while better facilitating their integration into the digital society.